Penerapan Digital Marketing berbasis Web Guna Pengembangan UMKM COMA - Putra, Aulia Darma Putra; Putri Indri Yani; Kurnia, Redha Kurnia; Novadilastri, Novadilastri; Sularno, Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2023)
The website is used as an electronic catalog that displays the products sold by the company. In this century every company must complete its means of communication by creating a website. The website is used as an electronic catalog that displays the products sold by the company. A company must continue to show their quality in selling products / Interviews are conducted directly with the owners of Coma MSMEs. History of MSMEs Coma the owner is a 2nd year student of the Telecommunications study program. MSME owners saw an opportunity and were inspired in addition to selling wallets, Coma MSMEs themselves have 3 types of products, namely Coma Bracelet, as a result the web can run according to the needs of business owners.